Foot Care Awareness among Diabetic Patients - Sheeraz Ali Jatoi, Mumtaz Ali Chhutto, Mujeeb-ur-Rehman Abro, Barkat Ali Dahar, Kouromal Gurbakhshani, Bakhtawar Guramani (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: To assess the awareness of the patient regarding foot care. Methodology: This retrospective study was conducted at Diabetes & Endocrinology Ward, Chandka Medical College Hospital, Shaheed Mohtarma Benazir Bhutto Medical University, Larkana from 1st January 2022 to 30th June 2022. There were 200 patients enrolled in this study suffering from type-2 diabetic patients with an age more than 30 years were included. A well-structured questionnaire was designed for documenting the awareness related questions about foot care from each diabetic patient. Patients were classified as those who have visited physician for foot care or not, ulceration presence, and risk status. Results: The mean age of the cases were 50.7±10.4 years with more males having no foot ulceration while higher females suffering from foot ulcerations. The educational status presented higher level of primary education in both groups while this was followed by no education in foot ulceration diabetic patients. The knowledge scores presented higher number of patients above age 45 having the knowledge of foot care with 127 females presented. The awareness of self-foot care was observed in on 45 cases with highest in those having at least secondary education. There were 45.5% those diabetic patients having long time history of diabetes. There were 9% cases with previous history of foot ulceration. The awareness of foot care practice was observed in 37.5% of the total cases with only 4 those having foot ulceration. There was very poor hygiene awareness about feet in cases with foot ulceration. Awareness about not soaking the feet was only present in 24% of ulceration foot diabetic patients while 34% were not aware of risks with walking barefoot outside. Those patients whose feet were examined by physicians had significantly higher trend of walking barefoot. They also were less aware of drying toes web spaces as compared to the other groups. Practical implication Conclusion: Diabetic foot ulceration was observed significantly low in those patients who had knowledge regarding self-care. Keywords: Foot ulcers, Diabetes, Neuropathy, Guidelines, Amputation